Certain Class of Analytic Functions Connected with q-Analogue of the Bessel Function. (13th April 2021) - Alessa, Nazek; Venkateswarlu, B.; Loganathan, K.; Karthik, T.S.; Reddy, P. Thirupathi; Sujatha, G.
Abstract : The focus of this article is the introduction of a new subclass of analytic functions involving q -analogue of the Bessel function and obtained coefficient inequities, growth and distortion properties, radii of close-to-convexity, and starlikeness, as well as convex linear combination. Furthermore, we discussed partial sums, convolution, and neighborhood properties for this defined class.